IMPACT ON TYPE LUCHNOHO FITOTSENOZU ENERGY RESERVES IN ABOVEGROUND VEGETATION MASS IN THE LEFT-BANK FOREST-STEPPE OF UKRAINE - Орлова, Л.Д. (World of Medicine and Biology, 2014)
It is noted that one of the main tasks determine the productivity of plant communities, including grassland, is the study of processes of growth and accumulation of plant matter and, accordingly, reserves of energy. Indicators of energy that Yu Odum aptly named "environmental currency" that underlie the structural-functional parameters, is a measure of the effectiveness of various processes of ecosystem functioning as a whole and their individual units. Assessment of the energy potential of stocks and flows of energy gives you the opportunity to reach regulation, optimal use of their and other Stocks and flows of energy are based on complex processes that occur in nature and, ultimately, ensure the circulation of all substances, the functioning of all ecosystems, life on our planet. Indicated that meadow phytocenoses of Left-Bank forest-Steppe of Ukraine is very heterogeneous in nature geomorphological and soil priurocheno, and water and air regime, floristic diversity and productivity. Therefore, the development of the forecast of their further transformation and sustainable use must be approached in a differentiated way, with all their features, including the accumulation of land mass and its energy potential. The objective of the work was to establish the number, the dynamics of the energy potential of the floodplain, upland, lowland meadows of the region and their dependence on environmental factors. Field studies were conducted on riparian, upland and lowland meadows, which are taken from different parts of the Left-Bank forest-Steppe of Ukraine. It is established that the investigated meadows energy in aboveground phytomass for all years of study were in the range of 2.1×106-17,5×106 j/m2. Analysis of the average energy accumulation in the studied meadows during 2008-2014, shows a smaller amount of it in the season with the worst weather conditions, particularly high temperatures and lack of precipitation. In the most unfavorable years energy reserves were 3, 8 times less than in the more favorable seasons. The energy potential of aboveground mass for individual types of onions over the years reveals a trend similar to the average accumulation of aboveground mass for all mixtures. Particularly low were indicators of energy storage in dry meadows. On the grass floodplain was also observed decline in some years, but not as sharp as the previous one. On lowland meadows fluctuations of energy reserves were less pronounced. Lowland meadows, unlike others, are characterized by a more constant moisture. On the formation of the grass greatly affect the floristic composition and part of the bow. On the floodplain of the largest energy reserves established on riverine and more often in the сentral part, on the dry valleys at the base of the slope, on the lowlands near the small cuts. In general, the energy stock in above-ground mass of the studied meadow herbage was higher when reducing economic pressures, i.e., the introduction of specific protection regime. This increase, depending on the type of meadow sward, was a third or a half more than in normal use.